Analysis of Green Accounting and Good Corporate Governance with Internal Audit Quality as a Moderating Variable on the Sustainability of Agribusiness Companies Listed on the Indonesian Stock Exchange in 2020-2022 - Rosady, Gempar; Lenggogeni, Lenggogeni; Yanti, Harti Budi (Dinasti Publisher, 2024)
This study aims to determine and obtain empirical evidence about the effect of the Green Accounting mechanism, Good Corporate Governance with Internal Audit Quality on the disclosure of Sustainability of agribusiness companies listed on the Indonesia Stock Exchange in 2020-2022. The Internal Audit Quality mechanism is assessed through education and training, experience in public accounting firms, and the application of the whistle blowing system. The Good Corporate Governance mechanism is assessed through managerial ownership, institutional ownership, and independent commissioners. Green Accounting measurement is based on the Public Disclosure Program for Environmental Compliance (PROPER) which is seen from the company's annual report and sustainability report. The samples that became the object of this research were all agribusiness companies listed on the Indonesia Stock Exchange in 2020-2022 by meeting the predetermined criteria. The total research sample for three years of observation was 132 samples, using purposive sampling method. Data analysis was carried out using multiple linear regression methods. The results of this study indicate that Green Accounting have an effect on Sustainability Diclosure and Good Corporate Governance with Internal Audit Quality doesn’t have an effect on Sustainability disclosure.